Odpowiedź :
h)
[tex][12\frac{1}{2}-\frac{1}{2}\cdot(5\frac{2}{3}+4\frac{5}{6})]:3\frac{3}{4} = [\frac{25}{2}-\frac{1}{2}\cdot(5\frac{4}{6}+4\frac{5}{6})]:\frac{15}{4} = (\frac{25}{2}-\frac{1}{2}\cdot9\frac{9}{6})\cdot\frac{4}{15}=\\\\\\=(\frac{25}{2}-\frac{1}{2}\cdot9\frac{3}{2})\cdot\frac{4}{15} = (\frac{25}{2}-\frac{1}{2}\cdot\frac{21}{2})\cdot\frac{4}{15} = (\frac{50}{4}-\frac{21}{4})\cdot\frac{4}{15}=\frac{29}{4}\cdot\frac{4}{15} =\frac{29}{15} = 1\frac{14}{15}[/tex]
Odpowiedź:
(12 i 1/2 - 1/2 * (5 i 2/3 + 4 i 5/6)) : 3 i 3/4 = (12 i 1/2 - 1/2 * (5 i 4/6 + 4 i 5/6)) : 3 i 3/4 = (12 i 1/2 - 1/2 * 9 i 9/6) : 3 i 3/4 = (12 i 1/2 - 1/2 * 63/6) : 3 i 3/4 = (12 i 1/2 - 63/12) : 3 i 3/4 = (12 i 1/2 - 5 i 3/12) : 3 i 3/4 = (12 i 6/12 - 5 i 3/12) : 3 i 3/4 = 7 i 3/12 : 3 i 3/4 = 87/12 : 15/4 = 87/12 * 4/15 = 87/45 = 1 i 42/45 = 1 i 14/15